BEYOND THE CLASSROOM: THE ROLE OF INFORMAL SPEAKING PRACTICE IN DEVELOPING ORAL PROFICIENCY IN UZBEKISTAN - To‘raliyeva Farzona Baxriddinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the significance of informal speaking practice outside formal classroom settings in enhancing oral proficiency among English language learners in Uzbekistan. While traditional classroom instruction emphasizes grammar and vocabulary, real-life conversational opportunities remain limited. The study examines how informal interactions, such as language clubs, social media engagement, and peer conversations, contribute to learners’ communicative competence. Findings suggest that integrating informal speaking activities alongside formal lessons can significantly boost learners’ confidence and fluency, thereby improving overall language acquisition. Moreover, the study highlights the importance of cultural context in shaping informal speaking opportunities, noting that Uzbek learners often face societal expectations and limited exposure to native speakers, which influence their informal practice. The article advocates for educational policies that recognize and support informal language use as a critical complement to formal instruction.